Evaluating the role of Artificial Intelligence in sustainable development goals with an emphasis on “quality education” - Hatoon S. AlSagri; Shahab Saquib Sohail (Discover Sustainability, 2024)
Abstract The integration of Artificial Intelligence (AI), particularly advancements in Generative AI technologies such as Large Language Models (LLMs)—of which ChatGPT is a notable example—marks a pivotal step in addressing global challenges within the framework of Sustainable Development Goals (SDGs). Specifically, within SDG4 (Quality Education), these open AI technologies have the potential to revolutionize education by providing scalable, personalized learning experiences, improving access to quality education, and optimizing resource allocation. By reducing barriers to educational equity and supporting lifelong learning, AI contributes not only to enhancing educational outcomes but also to the broader pillars of sustainability—social, economic, and environmental. Despite these promising applications, the existing literature reveals significant gaps in understanding the full scope of AI’s role in achieving SDGs. This study employs a bibliometric analysis to quantify the current research on AI’s contribution to sustainable development, with a particular focus on educational quality and sustainability. Our analysis highlights emerging trends, key contributors, and prevalent themes in the academic discourse, providing a robust foundation for future research. We argue that a deeper understanding of AI’s capabilities can inform more effective policies and strategic initiatives, fostering equitable and sustainable educational systems. Future research should further explore ethical considerations and long-term societal impacts of AI integration into education and other sectors. This study offers a comprehensive overview of the current research landscape, identifies critical areas for future investigation, and sets the stage for continued academic inquiry into AI and sustainability.